2012
DOI: 10.1177/0011000012442648
|View full text |Cite
|
Sign up to set email alerts
|

Effective and Ineffective Supervision

Abstract: Although supervision is recognized as a significant tenant of professional growth for counseling and psychotherapy students, the variability of the effectiveness, or ineffectiveness, of supervision has come under scrutiny in recent times. Our sample of 128 participants shed light on the most effective (e.g., encouraged autonomy, strengthened the supervisory relationship, and facilitated open discussion) and most ineffective (e.g., depreciated supervision, performed ineffective client conceptualization and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
171
0
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(193 citation statements)
references
References 27 publications
14
171
0
8
Order By: Relevance
“…Highlighting the importance of this subject matter may prompt supervisors to consider how they may facilitate optimal disclosure and reflect on their own disclosures with supervisees. It may also encourage supervisors to consider their role more fully in this professional relationship in order to create a facilitative learning environment, supportively address trainee anxiety and maximise supervisee professional development (Hess et al, 2008;Ladany et al, 1996) and ultimately benefit client outcomes (Ladany, Mori, & Mehr, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Highlighting the importance of this subject matter may prompt supervisors to consider how they may facilitate optimal disclosure and reflect on their own disclosures with supervisees. It may also encourage supervisors to consider their role more fully in this professional relationship in order to create a facilitative learning environment, supportively address trainee anxiety and maximise supervisee professional development (Hess et al, 2008;Ladany et al, 1996) and ultimately benefit client outcomes (Ladany, Mori, & Mehr, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It also encouraged more awareness of the group members' parallel processes, which, in turn, supported their reflective learning. This is mirrored in the research on effective and ineffective supervision done by Landany, Mori, and Mehr (2013), who found that the quantifiable variables under examination-such as supervisory working alliance, supervisor style, and supervisor (non)disclosure-were inextricably linked with and influenced the outcomes for both the therapy and the supervision process. Transference and countertransference (emotional reactions), along with interpretations by therapists and supervisors, can show how feelings, behavior, and expressions toward them are based on parallel processes (Cassoni, 2007;Clarkson, 1991;Cornell & Landaiche, 2006).…”
Section: Review Of the Supervision Literaturementioning
confidence: 85%
“…For these and other reasons, trainees may hesitate to seek timely consultation with a supervisor, especially during a clinical session. These findings reiterate the importance of developing an effective supervisory alliance (Ladany, Mori, & Mehr, 2013) so that trainees will follow the simple guidelines: "When in doubt, consult," and "If one wonders whether or not to bring something up in supervision, bring it up." On those occasions when a supervisor is not imme diately available, arrangements need to have been made in advance for how to access timely consultation.…”
Section: R Ecognizing Ethical and Legal Issues And Prioritizing Dutiementioning
confidence: 88%